Comparison of Three Surgical Options for Treatment of Diaphyseal Tibia Fractures in Pediatric Patients - Sang Won Lee, MSc; Blair Stewig, BSc; Danielle Cook, MA; Kristin Alves, MD, MPH; Akossiwa Brynn Assignon, MA; Daniel Hedequist, MD; Mininder S. Kocher, MD, MPH; Benjamin J. Shore, MD, MPH, FRCSC; Susan T. Mahan, MD, MPH (Journal of the Pediatric Orthopaedic Society of North America, 2025)
Background: Most pediatric diaphyseal tibia fractures can be treated with reduction and casting. While surgical reduction and fixation are sometimes necessary, there is no clear consensus about the optimal implant. Plate osteosynthesis (PO), elastic intramedullary nailing (EIN), and multiplanar external fixation (MEF) are common surgical fixation methods in the skeletally immature patient after failing closed reduction. This study aims to compare the indications and outcomes of PO, EIN, and MEF techniques for the surgical treatment of the pediatric diaphyseal tibia fracture. Methods: Skeletally immature patients ages 4–16 years treated surgically by PO, EIN, or MEF for a diaphyseal tibia fracture at a single, tertiary pediatric hospital were included. Demographic, clinical, radiographic data, and complications were collected retrospectively. Complications were classified according to the Clavien-Dindo-Sink classification. Results: In total, 82 patients were included with a median age of 13.4 years (range, 5.69–15.94) and median follow-up of 46 weeks (range, 14–237), of whom 84% (69/82) were male. Most patients received EIN (61%; 50/82), while 23% (19/82) had MEF, and 16% (13/82) had PO. There were no differences across treatment groups for open (P = .96) and comminuted (P = .19) fractures. Location of fracture was significantly different by treatment method, with middle 1/3 fractures treated mostly by EIN (77%; 34/44) and distal 1/3 fractures treated across all three fixation methods (P = .002). Patients treated with MEF (47%; 9/19) and PO (46%; 6/13) had higher complication rates compared with those treated with EIN (22%; 11/50). Patients treated with PO and MEF had 6.0 and 6.2 times the odds of having a severe complication, compared to patients who had EIN, controlling for age, weight, and fracture severity (P = .01, P = .02). There was no significant difference in other fracture characteristics and outcomes. Conclusion: All three fixation types (PO, EIN, and MEF) show similar indications, although fracture location in the diaphysis may influence implant choice. EIN has a lower complication rate compared with PO and MEF and presents a strong option for operative treatment of the pediatric tibia shaft fracture. Key Concepts: (1) There is no clear consensus about optimal implant, including plate osteosynthesis (PO), elastic intramedullary nailing (EIN), and multiplanar external fixation (MEF), for the surgical treatment of skeletally immature tibial shaft fractures. (2) Among 82 patients with pediatric tibial diaphysis fractures, most patients received EIN (61%; 50/82), while 23% (19/82) had MEF, and 16% (13/82) had PO with no difference across treatment groups in terms of open (P = .96) or comminuted (P = .19) fractures. (3) Location of fracture was significantly different by treatment method, with middle 1/3 fractures treated mostly by EIN (77%; 34/44) and distal 1/3 fractures treated across all three fixation methods (P = .002). (4) Patients treated with EIN (22%; 11/50) had a lower complication rate compared with those treated with MEF (47%; 9/19) and PO (46%; 6/13). Patients treated with PO and MEF had 6.0 and 6.2 times the odds of having a severe complication compared with those treated with EIN, controlling for age, weight, and fracture severity (P = .01, P = .02). (5) All three fixation types show similar indications, although fracture location in the diaphysis may influence implant choice, and EIN presents a strong option for operative treatment of the pediatric tibia shaft fracture with a lower complication rate. Level of Evidence: Level III: Case-control study or retrospective cohort study